The global politics of social protection - Sam Hickey; Jeremy Seekings (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Since the early 2000s international development agencies have actively promoted social protection as a new global public policy. This process can be understood as flowing from related shifts within the global political economy and of development ideology, and involved international development agencies deploying strategies of governmentality to 'render technical' social protection, and cash transfers in particular, as the logical solution to myriad development problems, including within Africa. The paper places this move in historical perspective and examines the role that a particular aid agency played in shaping the transfer of cash transfers to Africa.
Keywords: 330; Africa; policy transfer; politics; social protection